1977
DOI: 10.1080/02626667709491704
|View full text |Cite
|
Sign up to set email alerts
|

THECEQUEAUMODEL: DESCRIPTION AND EXAMPLES OF ITS USE IN PROBLEMS RELATED TO WATER RESOURCE MANAGEMENT / Le modèle CEQUEAU: description et exemples d'utilisation dans le cadre de problèmes reliés à l'aménagement

Abstract: Because the CEQUEAU hydrophysiographic model is able to simulate natural or modified discharges simultaneously in time and space, it is suited to multiple applications. By using such a model, one can study the hydrological repercussions, all over a basin, resulting from natural or man-made modifications to its characteristics. For instance, the various effects originating from the site, type and characteristics of intended dams (flood control, diversion, storage, etc.) can be simulated with satisfaction. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…For example, Abaza et al (2015) assimilated streamflow at the outlet using the EnKF to update two state variables (soil moisture in the intermediate and deep layers of the hydrological model used in their study) using a time step of 3 h. The resulting gain in CRPS was high for the first time step and decreased quickly as a function of the forecast horizon such that mainly the first 24 h benefited from the data assimilation. Chen et al (2013) found similar results with multiple performance criteria when assimilating streamflow using a variant of the EnKF (the ensemble square root filter) to update various state variables represented by conceptual reservoirs. The observed improvement duration was even shorter, lasting less than 12 h during flash flood events.…”
Section: Streamflow Data Assimilationsupporting
confidence: 54%
“…For example, Abaza et al (2015) assimilated streamflow at the outlet using the EnKF to update two state variables (soil moisture in the intermediate and deep layers of the hydrological model used in their study) using a time step of 3 h. The resulting gain in CRPS was high for the first time step and decreased quickly as a function of the forecast horizon such that mainly the first 24 h benefited from the data assimilation. Chen et al (2013) found similar results with multiple performance criteria when assimilating streamflow using a variant of the EnKF (the ensemble square root filter) to update various state variables represented by conceptual reservoirs. The observed improvement duration was even shorter, lasting less than 12 h during flash flood events.…”
Section: Streamflow Data Assimilationsupporting
confidence: 54%
“…CEQUEAU is a grid-based distributed hydrologic model with a modular structure allowing to select snowmelt and evapotranspiration formulations to compute runoff availability (Charbonneau et al, 1977). The flow routing is based on a cell-to-cell approach that is calibrated using time delays from one cell to the next.…”
Section: Hydrologic Model Cequeaumentioning
confidence: 99%
“…1) The hydrological model CEQUEAU (Charbonneau et al, 1977) is calibrated on each of the five sub-basins using the Dynamically Dimensioned Search algorithm (DDS) (Tolson and Shoemaker, 2007) according to the procedure in Arsenault et al (2014). CEQUEAU is a grid-based distributed model which is set up on a 10km resolution grid on the SLSJ basin.…”
Section: Preparation Of Esp Forecastsmentioning
confidence: 99%